Development of a scale for students in evaluating 2017 information technology and software curriculum - Demir, Elif Buğra Kuzu; GÜNDÜZ, GÜLTEN FERYAL (ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, ESKISEHIR, 26480, TURKEY, 2019)
The purpose of this study was to develop a valid and reliable instrument measuring the views of secondary school 5th grade students on the curriculum of 2017 Information Technology and Software (ITS) course. The study was carried out with 528 5th grade students (15 for pilot application, 320 for exploratory factor analysis (EFA), 203 for confirmatory factor analysis (CFA) studying in the spring semester of 2017-2018 school year. Implementation of the scale was realized with participants who were determined through the combination of criterion and convenience sampling. In order to determine the content validity and face validity of the scale, expert opinions were obtained, while both EFA and CFA were performed to assess the construct validity of the scale's measures. Analyses revealed one-factor structure which sheltered 30 items, which explained 39.92 percent of the total variance with a high internal consistency coefficient. The CFA on the one-factor structure revealed acceptable fit indices as well. Based on these findings, it could be concluded that the scale is an instrument that produces valid and reliable measures, and that can be used to determine fifth grade students' views on the curriculum evaluation of 2017 ITS course. For further studies, the scale can be implemented to a random sample form the population of 5th grade students to reveal their views on the curriculum and studies can be conducted in order to investigate in terms of different variables.
Keywords: Curriculum; Curriculum of Information Technologies and Software Course; Secondary Schools; Curriculum Evaluation; Scale Development